In situ and invasive carcinoma identified through an opportunistic screening mammography in asymptomatic women of Mexico City. - Nancy Reynoso-Noverón; Yolanda Villaseñor-Navarro; Mauricio Hernández-Ávila; Alejandro Mohar-Betancourt (Instituto Nacional de Salud Pública, 2013)
Objective. To describe the mammographic findings and carcinoma detection rate in asymptomatic women of Mexico City, that participated in an opportunistic screening program. Materials and methods. 39 491 participants were included, with mammograms performed and interpreted in the National Cancer Institute, from 2008 to 2011. The mammographic findings, type of lesion and true positives (TP), are described by age groups. We calculated the crude effect of age on the classification BIRADS (Breast Imaging Reporting and Data System) 0 and the type of lesion. Results. The median age was 50 (45-57) years. 80.5% were classified as BIRADS 2, 11.4%(0), 4.1%(1), 3.5%(3), 0.5%(4) y 0.1%(5). Malignant lesions were detected in 1.3 and 3.3 per 1000 and the proportion of true positives (TP) was 8.2% and 20.6%, in women of 41-50 and 51-70 years, respectively. Conclusions. Although some cases are detected in women 40 to 50 years, in women over 50 years the screening by mammography is more efficient, with a higher proportion of cases detected and fewer false positives.